Níveis séricos de cortisol e 17-& estradiol durante o ciclo estral em marrãs (Sus domestica - Linnaeus 1758) - Toniollo, G. H.; Vicente, WRR; Oliveira, C. A.; Malheiros, E. B.; Carvalho, LFOS (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1997)
In the present study 21 young swine females, sexually mature, reared and kept under an industrial management system were assessed for cortisol and oestradiol-17 beta serum prolifes during the oestrus cycle. Blood sampling was performed always at the same interval, from 8:00 to 10:00 a.m. Each animal was submitted to 14 venal punctions at days 0, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 21, 22 and 23 of the oestrous cycle. The first day of the oestrous phase was assumed to be day 0 and the 23(rd) as the first of the next cycle. Hormone determinations were performed using a solid phase radioimmunoassay (RIA). Regarding to cortisol concentrations, there was a variation from 3.5 to 8.0 mu g/dl and for oestradiol-17 beta the mean values detected varied from 3.5 to 14.9pg/ml.
Cortisol and oestradiol-17 beta serum levels during the oestrus cycle in gilts (Sus scrofa domestica Linnaeus 1758).
Keywords: Cortisol; 17 beta oestradiol; serum level; swine